PROSES NEGOSIASI PEREMPUAN WIRAUSAHA AGRIBISNIS PANGAN BERDASARKAN PENDEKATAN SISTEM AGRIBISNIS DI KOTA BOGOR - Yusalina Yusalina; Rachmat Pambudy (Jurnal Ilmu Komunikasi Acta Diurna, 2018)
The aims of the study are to describe negotiation process and to find how women entrepreneursinterpret their negotiations. This study was based on interpretive paradigm with phenomenologicalapproach that resulted in qualitative data. The selected subject consisted of 16 women entrepreneursof food agribusiness in Bogor City. The data were obtained through in-depth interviews, observationand document analysis. The results show that both formal and informal negotiation process whichinvolves people/parties with various interests. The success of negotiation process is affected bynegotiation strategies, such as time, location, media communication, and distributive and integrativestrategies.